Quantitative analysis of neutralizing immune responses to human parvovirus B19 using a novel reverse transcriptase-polymerase chain reaction-based assay - Bostic, J R; Brown, K E; Young, N S; Koenig, S (The Journal of infectious diseases, 1999)
Infection with human parvovirus B19 causes fifth disease, acute and chronic red cell aplasia, fetal hydrops, arthropathy, and other disorders. Antiviral antibodies limit B19 infection in vivo; however, the identification of serologic markers of protection has been hampered by the lack of a quantitative assay for parvovirus neutralization. A novel in vitro test for parvovirus neutralization has been developed using reverse transcriptase-polymerase chain reaction to detect viral transcripts in a B19-permissive cell line. Parvovirus neutralizing activity was measured in sera from naturally infected individuals, and common features of sera with high neutralizing capacity were identified as protection correlates. Sera that suppressed B19 replication in vitro demonstrated IgG reactivity with capsid proteins VP1 and VP2, but no linear relationship between antibody titer and neutralizing capacity was observed. Sera from experimental animals and human volunteers immunized with a virus-like particle vaccine candidate exhibited B19 neutralizing titers equal to or greater than those observed in natural infections.